2021
DOI: 10.1038/s41419-021-04151-3
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α synergises with IFN-γ to induce caspase-8-JAK1/2-STAT1-dependent death of intestinal epithelial cells

Abstract: Rewiring of host cytokine networks is a key feature of inflammatory bowel diseases (IBD) such as Crohn’s disease (CD). Th1-type cytokines—IFN-γ and TNF-α—occupy critical nodes within these networks and both are associated with disruption of gut epithelial barrier function. This may be due to their ability to synergistically trigger the death of intestinal epithelial cells (IECs) via largely unknown mechanisms. In this study, through unbiased kinome RNAi and drug repurposing screens we identified JAK1/2 kinases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 91 publications
0
46
0
1
Order By: Relevance
“…IFN-activated JAK/STAT signaling induced the robust expression of ZBP1, which complexed with RIPK3 to trigger MLKL-driven necroptosis ( Ingram et al, 2019 ). Similarly, TNF-α synergized with IFN-γ could induce epithelial cell necroptosis through the CASP8-JAK1/2-STAT1 module ( Woznicki et al, 2021 ). Taken together, we speculated that necroptosis probably contributed to the occurrence and development of LUAD through the JAK/STAT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-activated JAK/STAT signaling induced the robust expression of ZBP1, which complexed with RIPK3 to trigger MLKL-driven necroptosis ( Ingram et al, 2019 ). Similarly, TNF-α synergized with IFN-γ could induce epithelial cell necroptosis through the CASP8-JAK1/2-STAT1 module ( Woznicki et al, 2021 ). Taken together, we speculated that necroptosis probably contributed to the occurrence and development of LUAD through the JAK/STAT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Research confirmed that the proinflammatory response is one of the mechanisms of intestinal epithelial injury [ 7 ]. Furthermore, as the classical proinflammatory cytokines, TNF- α and INF- γ could directly lead to intestinal epithelial damage [ 8 ]. The release of the proinflammatory cytokines in the intestinal tract is mainly regulated through the TLR4 pathway [ 9 , 10 ], which could be activated by bacteria and its related product lipopolysaccharide (LPS) [ 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results show an enhanced susceptibility of goblet-like HT29-MTX-E12 cells towards inflammation-mediated cytotoxicity, compared to enterocyte-like Caco-2 cells. Strong synergistic cytotoxicity of TNF-a and IFN-g towards HT29 cells has been described previously (46,47). For our investigations, a high dose of IFN-g is used to initially activate the THP-1 cells, so it is unlikely that the concentration of this cytokine differs significantly between the three inflamed cultures.…”
Section: Discussionmentioning
confidence: 82%